2018
DOI: 10.3762/bjoc.14.159
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and X-ray structure of 2-iodoxybenzenesulfonic acid (IBS) – a powerful hypervalent iodine(V) oxidant

Abstract: The selective preparation of 2-iodoxybenzenesulfonic acid (IBS, as potassium or sodium salts) by oxidation of sodium 2-iodobenzenesulfonate with Oxone or sodium periodate in water is reported. The single crystal X-ray diffraction analysis reveals a complex polymeric structure consisting of three units of IBS as potassium salt and one unit of 2-iodoxybenzenesulfonic acid linked together by relatively strong I=O···I intermolecular interactions. Furthermore, a new method for the preparation of the reduced form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…3A ). The crystal structure of 1 is uncommon among the known hypervalent iodine structures that have been characterized to date, with a pentavalent I(2) atom and a trivalent I(1) atom coexisting in one molecule via connection of an O(3) atom 17,28 ( Fig. 3B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A ). The crystal structure of 1 is uncommon among the known hypervalent iodine structures that have been characterized to date, with a pentavalent I(2) atom and a trivalent I(1) atom coexisting in one molecule via connection of an O(3) atom 17,28 ( Fig. 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…The existing hypervalent iodine( iii ) reagents include phenyliodine diacetate (PIDA), phenyliodine bis(trifloroacetate) (PIFA), iodosylbenzene (PhIO), [hydroxyl(tosyloxy)iodo]benzene (HTIB, Koser reagent), 4 PhICl 2 , 5 TolIF 2 , 6 diaryl iodonium salts, 7 Togni's reagents, 8 μ-oxobis(trifluoroacetoxyiodobenzene) (μ-oxo BTI), 9 cyano(trifluoromethylsulfonyloxy)iodobenzene (Stang's reagent), 10 1-phenyl-2-(phenyl-λ 3 -iodaneylidene)-2-((trifluoromethyl)sulfon-yl)ethan-1-one (Shibata reagent II), 11 iodosodilactone, 1 e etc. 12 The more widely studied hypervalent iodine( v ) regents mainly include 2-iodoxybenzoic acid (IBX), 13 Dess–Martin periodinane (DMP), 14 Hara reagent, 15 pentafluorophenyliodine tetrafluoride (PFITF), 16 2-iodoxybenzenesulfonic acid (IBS), 17 iodine pentafluoride, 18 iodoxybenzene, 19 and diaryliodosyl salts 20 ( Fig. 1 ).…”
Section: Introductionsmentioning
confidence: 99%
“…According to elemental analysis, a sample of product 4 prepared by recrystallization in open air is a complex of IBX with two molecules of trifluoromethanesulfonic acid. 1 H NMR spectrum of triflate 4 displayed signals in the aromatic region corresponding to the benziodoxole unit, while 13 C NMR displayed the signal of C-I(V) at about 147 ppm, which is typical of organoiodine(V) derivatives. X-ray crystallographic study of a single crystal 4 revealed a complex structure characterized by numerous intramolecular and intermolecular secondary contacts in a solid state ( Fig.…”
mentioning
confidence: 99%
“…In a search for the more powerful iodine(V) oxidants, several IBX modifications have been synthesized and investigated. [12][13][14][15][16] The most notable powerful iodine(V) oxidants are represented by the highly electrophilic IBX-tosylate and IBX-OTs diacetate 3, 16 which show high reactivity in the oxidation of structurally complex primary and secondary alcohols. 17 In the present communication, we want to report the preparation, structure and reactivity of IBX-ditriflate 4, the most powerful oxidant in the series of structurally similar IBX derivatives ( Fig.…”
mentioning
confidence: 99%
“… 1 H NMR aromatic region of 20 mM PhI-sulfonic acid, 100 mM LiClO 4 supporting electrolyte with 10% added water (v/v%) showing peaks before electrolysis and after 19, 59, and 120 C of charge passed and the same 120 C solution aged 2 days. 1 H NMR peaks for IBA- and IBX-sulfonic acid match the literature. ,, † The theoretical yield for IBX-sulfonic acid was determined assuming full conversion to IBX-sulfonic acid (i.e., 4e – /molecule). See the Supporting Information for a sample calculation of the Faradaic efficiency and additional discussion.…”
Section: Results and Discussionmentioning
confidence: 65%